Financial Liberalization and the Information Content of Money in Indonesia, Korea, and the Philippines - Hamann, A. (IMF Working Papers; Working Paper, 1993)
Using a VAR approach, this paper studies the relationship between money, output, and prices in a group of Pacific Basin countries that underwent financial sector reform during the 1980s: Indonesia, Korea, and the Philippines. Special attention is paid to assessing the information content of money. Money was found to contain valuable advance information on output and prices in Korea, on prices only in the Philippines, and did not contain any advance information in Indonesia. The introduction of financial sector reform was not found to lead to a structural break in the price and output equations; however, the information content of money was affected. Further tests show that exchange and interest rates-variables that gained flexibility with the reforms-contain valuable information about future developments in prices in Korea and the Philippines.